Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan (Studi pada PT. Indosat Persero Tbk Semarang : Gerai Indosat Ooredo Hutchison Semarang) - Saputro, Bagas Catur; Yunianto, Askar (IPM2KPE, 2024)
This study aims to analyze the influence of leadership style, work environment, and work motivation on employee performance at PT. Indosat Persero Tbk Semarang (Indosat Ooredo Hutchison Pandanaran Outlet). As one of the important factors in human resources, employee performance plays a crucial role in achieving company goals. Primary data were obtained through questionnaires distributed to 110 employees selected using purposive sampling techniques. The analysis methods include validity testing with factor analysis, reliability testing using Cronbach Alpha, and hypothesis testing with multiple regression analysis. The results of the study indicate that leadership style, work environment, and work motivation have a positive and significant influence on employee performance. Keywords: Leadership Style, Employee Performance, Work Environment, Work Motivation